Validation of the Italian version of the Charcot‐Marie‐Tooth disease Pediatric Scale. Issue 2 (26th May 2020) - Zuccarino, Riccardo; Prada, Valeria; Moroni, Isabella; Pagliano, Emanuela; Foscan, Maria; Robbiano, Giulia; Pisciotta, Chiara; Cornett, Kayla; Shy, Rosemary; Schenone, Angelo; Pareyson, Davide; Shy, Michael; et al.
Abstract: The Charcot‐Marie‐Tooth disease Pediatric Scale (CMTPedS) is a Rasch‐built clinical outcome measure of disease severity. It is valid, reliable, and responsive to change for children and adolescents aged 3 to 20 years. The aim of this study was to translate and validate an Italian version of the CMTPedS using a validated framework of transcultural adaptation. The CMTPedS (Italian) was translated and culturally adapted from source into Italian by two experts in CMT with good English language proficiency. The two translations were reviewed by a panel of experts in CMT. The agreed provisional version was back translated into English by a professional translator. The definitive Italian version was developed during a consensus teleconference by the same panel. CMT patients were assessed with the final version of the outcome measure and a subset had a second assessment after 2 weeks to evaluate test‐retest reliability. Seventeen patients with CMT aged 5 to 20 years (eight female) were evaluated with the CMTPedS (Italian), and test‐retest was performed in three patients. The CMTPedS (Italian) showed a high test‐retest reliability. No patient had difficulty in completing the scale. The instructions for the different items were clearly understood by clinicians and therefore the administration of the outcome measure was straight forward and easily understood by the children assessed. The CMTPedS (Italian) will be used for clinical follow‐up and in clinical research studies in the Italian population. The data is fully comparable to that obtained from the English language version.